Calamitic Liquid Crystals as Additive Materials to the Organic Solar Cells - Canli, N. Yilmaz; Boroglu, M. Safak (AMER SCIENTIFIC PUBLISHERS, 2016)
A bilayer polymer solar cell has been shown with the device configuration ITO/PEDOT:PSS/P3HT(poly(3-hexyl-thiophene))/C60/Al. In this article we have been reported the effect of two different liquid crystals which have different terminal chains to the bilayer organic solar cells. Based on photovoltaic measurements, we have been compared the efficiency enhancement for bilayer heterojunction solar cells using calamitic liquid crystals (LC1 and LC2). In this respect current-voltage characteristics of devices have been compared with LC1 and LC2. It has been determined that adding LC1 and LC2 increases the device parameters of bilayers. It has been also understood that the fill factor (FF) of the device has been significantly increased from 0.35 to 0.48 with adding LC1 which contain oxygen.
Keywords: P3HT:C60; Organic Photovoltaic (OPV); Solar Cells; LC; Power Conversion Efficiency (PCE); POSTPRODUCTION TREATMENT; POLYMER; EFFICIENCY; POLY(3-HEXYLTHIOPHENE); PHTHALOCYANINE; PHOTODIODES; CONVERSION; COMPOUND; BLENDS; Engineering; Science & Technology - Other Topics; Physics